APLIKASI Dolichoderus sp. UNTUK PENGENDALIAN Helopeltis spp. PADA TANAMAN KAKAO - Andi Ridwan; Ahdin Gassa; Tamrin Abdullah (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2020)
ABSTRAK An activity which aim to improve the Dolichoderus sp function in controlled Helopeltis spp which has been implemented in public cocoa garden. The activity is set two artificial nest each at two contrast side on cocoa branch. Result of study is show that cocoa tree after three months of the artificial nest installation the level of Helopeltis spp attack is run in to lower is being 8,86% by first time before artificial nest installation the level of Helopeltis attack is 46,6%. The artificial nest is very help to increase the Dolichoderus sp population. Which knowing as the predator or Helopeltis spp natural enemy on cocoa tree.